Next of kin [videorecording (DVD)] - Swayze, Patrick; Baldwin, Adam, 1962-; Hunt, Helen, 1963-; Paxton, Bill; Neeson, Liam (Warner Home Video, 1998)
Truman Gates, a cop from Appalachia, hunts for his brother's killers in Chicago.